2016
DOI: 10.1111/1750-3841.13364
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Slightly Acidic Electrolyzed Water and UV‐Ozonated Water Combination for Inactivating Escherichia Coli O157:H7 on Romaine and Iceberg Lettuce during Spray Washing Process

Abstract: Spray washing is a common sanitizing method for the fresh produce industry. The purpose of this research was to investigate the antimicrobial effect of spraying slightly acidic electrolyzed water (SAEW) and a combination of ozonated water with ultraviolet (UV) in reducing Escherichia coli O157:H7 on romaine and iceberg lettuces. Both romaine and iceberg lettuces were spot inoculated with 100 μL of a 3 strain mixture of E. coli O157:H7 to achieve an inoculum of 6 log CFU/g on lettuce. A strong antimicrobial eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
3
0
4
Order By: Relevance
“…Dessa forma, não foi possível inferir sobre a capacidade do ozônio de inativar Salmonella spp., coliformes totais e E. coli em morangos, no presente trabalho. Entretanto, Pang & Hung (2016) demonstraram que uma combinação de radiação UV e água ozonizada foi capaz de alcançar uma redução em torno de 5,00 ciclos log na contagem de E. coli O157:H7, em alface romana, enquanto os tratamentos com radiação UV e água ozonizada, isoladamente, possibilitaram reduções de 2,10 e 2,70 ciclos log, respectivamente.…”
Section: Concentração (Mg L -1 ) Equações Ajustadas Runclassified
See 2 more Smart Citations
“…Dessa forma, não foi possível inferir sobre a capacidade do ozônio de inativar Salmonella spp., coliformes totais e E. coli em morangos, no presente trabalho. Entretanto, Pang & Hung (2016) demonstraram que uma combinação de radiação UV e água ozonizada foi capaz de alcançar uma redução em torno de 5,00 ciclos log na contagem de E. coli O157:H7, em alface romana, enquanto os tratamentos com radiação UV e água ozonizada, isoladamente, possibilitaram reduções de 2,10 e 2,70 ciclos log, respectivamente.…”
Section: Concentração (Mg L -1 ) Equações Ajustadas Runclassified
“…Microrganismos, como aeróbios mesófilos, do grupo coliformes, bolores e leveduras, são encontrados geralmente em produtos in natura e minimamente processados, em concentrações que variam de 10 3 a 10 9 UFC g 1 , sendo responsáveis tanto pela deterioração da qualidade físico-química como pelo risco à saúde dos consumidores (Tournas & Katsoudas, 2005;Abadias et al, 2008;Alexandre et al, 2011;Pang & Hung, 2016). Nesse contexto, o morango esteve associado a surtos de hepatite A, além de contaminação por Norovírus, Cyclospora cayatanensis e Staphylococcus aureus (Notermans et al, 2004;Sivapalasingam et al, 2004).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Pang and Hung (2016) demonstrated that a combination of UV radiation and ozonated water can achieve a reduction of 5 log cycles in the E. coli O157:H7 count in romaine and iceberg lettuces, whereas the treatment with UV radiation only obtained a reduction of 2.1 log cycles and treatment with a chlorine solution a reduction of 2.5 log cycles. Aguayo et al (2013) reported that ozonated water with a concentration of 0.4 mg L -1 and three immersion times of 1, 3 and 5 min could effectively reduce the concentration of mesophilic bacteria in tomato fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Electrolyzed water (EW) has been approved as a food sanitizer by the Food and Drug Administration (Hsu, , ; Huang, Hung, Hsu, Huang, & Hwang, ; Liu, Tan, Yang, & Wang, ; Liu, Wu, Lim, Yang, & Wang, ; Park, Guo, Rahman, Ahn, & Oh, ; Zhang, & Yang, ; Zhang, Zhou, Chen, & Yang, ). It has been reported to possess antimicrobial activity against a variety of microorganisms (Hao et al., ; Huang et al., ; Liu et al., ; Pang, & Hung, ; Sow, Tirtawinata, Yang, Shao, & Wang, ; Zhang, Li, Jadeja, & Hung, ). However, at low pH, EW is corrosive, has a short shelf life, might be toxic to operators, and cause corrosion of different types of metals.…”
Section: Introductionmentioning
confidence: 99%